Multiomics identify the gene expression signature of the spinal cord during aging process - Lintao Xu; Jingyu Wang; Jinjie Zhong; Weiwei Lin; Gerong Shen; Ning He; Xingjia Mao; Chunyan Fu; Zhaobo Huang; Fengdong Zhao; Xin Ye; Yongjian Zhu; et al. (Communications Biology)
Abstract Age-related long-term disability is attracting increasing attention due to the growing ageing population worldwide. However, the current understanding of the senescent spinal cord remains insufficient. Bulk RNA sequencing reveals that 526 genes are upregulated and 300 genes are downregulated in senescent spinal cords. Pathway enrichment analysis of differentially expressed genes shows that senescence in spinal cords is related to phagosome function, neuroinflammation, ferroptosis, and necroptosis. Prediction of upstream transcription factors and interactome analysis identify Spi1 as a transcription factor that potentially plays a core role in senescent spinal cords. Spatial transcriptomics illustrates the spatial distribution of the transcriptomic landscape in both young and senescent spinal cords and identifies distinct neuronal and glial subtypes. The ferroptosis-associated gene Fth1 is upregulated in aged spinal cords. Flow cytometry reveals increased accumulation of free Fe2+ and ROS in senescent mixed glial cells; however, CCK-8 assays reveal that these cells are resistant to ferroptosis. SiRNA and lentivirus experiments indicate that the overexpression of Fth1 in normal mixed glial cells reduces their sensitivity to ferroptosis, whereas Fth1 knockdown increases their sensitivity to ferroptosis. In summary, spatial and bulk transcriptomics elucidate the transcriptional characteristics of young versus senescent spinal cords, thus highlighting the role of Fth1 in mediating ferroptosis resistance in senescent mixed glial cells.